Impact of different treatments on the antioxidant properties of two market types of peanuts grown in Mexico - M.C. Robles-Ramírez; R. Viramontes-Bocanegra; R. Mora-Escobedo; E. Ortega-Robles; M.C. Beltrán-Orozco (Grasas y Aceites, 2023)
The effect of roasting, frying, microwave heating, and germination on the antioxidant properties, total phenolics and flavonoids content of two types of peanuts (Valencia and Virginia) grown in Mexico was investigated. The thermal treatments affected the phenolic content and the antioxidant capacity of the two varieties of peanuts differently (by ABTS, DPPH, FRAP and iron chelating activity methods). Germination was the best method to increase the antioxidant activity (up to 157% increase in the Virginia variety) and the contents of compounds with nutraceutical potential in the peanuts (up to 59% increase in total phenolics in the Valencia variety and 700% increase in total flavonoids in the Virginia variety). Germinated peanuts could be used as raw material for the production of functional foods.